The Influence of Gamification on Problem Based Learning in Improving the Quality of Physical Education and Sports Learning at the Elementary School Level: Motivational Formation of Social and Cultural Character in Rural Papua Indonesia - Carolus Wasa; Adi Sumarsono; Thadius Yambedoan; Dani Nurcholis (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2025)
This study analyzes the effect of Gamification Based Learning (GBL) on creative thinking ability and collaborative skills of students in rural Papua. By using 27 elementary schools in rural papua indonesia. data taken directly in the field through valid test results without flaws, this study ensures that all variables, including increasing the motivation of social character of students in rural papua with the application of gamification in sports learning are filled in completely, and can provide valid data. The results of the analysis showed that the application of gamification in sports learning significantly increased students' creativity. Hypothesis testing using t-statistics showed a significance value (p-value) of 0.000, well below the threshold0.005, indicating a significant difference between the experimental and control classes. In the experimental class, 100% of students moved to the "very creative" category after the implementation of gamification, while the control class showed a less encouraging distribution of scores. The process stages in GBL, integrated with gamification elements such as achievements and a supportive atmosphere, encouraged students to participate more actively. In addition, the study found that gamification also improved collaborative skills, with 50% of students in the experimental class being in the "highly collaborative" category after the treatment. However, challenges such as difficult classroom dynamics require good management from the teacher. This research emphasizes the importance of implementing gamification in increasing student engagement and motivation, as well as providing significant results in cognitive and collaborative aspects, which is highly relevant in the context of education in Papua Indonesia.